Nicotine Use Awareness and Nicotine Insight Scale in Addicts: A Turkish Validity–Reliability Study - Oznur Muz, Feyza Nehir; Metintas, Selma; Onsuz, Muhammed Fatih; Sungur, Sevda; Tepetas, Mine; Akdag, Zehra (Addicta: The Turkish Journal on Addictions, 2024)
Abstract: One of the first steps in tobacco addiction treatment is gaining insight into whether the individual has a problem with nicotine use and realizing the need for cessation treatment. This study is a methodological study describing the cultural adaptation of the Nicotine Use Awareness and Insight Scale and evaluating its Turkish validity and reliability. Linguistic validation was carefully performed through forward and backward translation. The study group consisted of 368 individuals who were confirmed to be tobaccodependent by scoring four or higher on the The Fagerström Test for Nicotine Dependence. A strong positive correlation was found between Nicotine Use Awareness and Insight Scale and Stages of Change Readiness and Treatment Eagerness Scale scores, used for equivalent criterion (predictive) validity. Cronbach’s α coefficient was 0.85. Exploratory factor analysis showed that the scale explained 52.7% of the total variance with a single-factor structure. Nicotine Use Awareness and Insight Scale, a reliable and valid scale for Turkish people, can be utilized in studies aimed at raising awareness and raising consciousness among addicted individuals.